profile
Опубликовано 1 год назад по предмету Алгебра от ABC1234567

упростите выражение:
 frac{ a^{ frac{1}{2} } +  b^{ frac{1}{2} }  }{ a^{ frac{1}{2} } } -  frac{ a^{  frac{1}{2} } }{ a^{ frac{1}{2} } -  b^{ frac{1}{2} }  } +  frac{b}{a -  a^{ frac{1}{2} } b^{ { frac{1}{2} } }  }

  1. Ответ
    Ответ дан Artem112
     frac{a^{ frac{1}{2}}+b^{ frac{1}{2} } }{ a^{ frac{1}{2} } } - frac{ a^{ frac{1}{2} } }{ a^{ frac{1}{2} } - b^{ frac{1}{2}}}+frac{b}{a-a^{ frac{1}{2}}b^{{frac{1}{2}}}}=
 frac{sqrt{a}+sqrt{b} }{  sqrt{a}}-frac{sqrt{a}  }{  sqrt{a}-sqrt{b} } + frac{b}{ sqrt{a}( sqrt{a}-sqrt{b})}}=
\
= frac{(sqrt{a}+ sqrt{b})(sqrt{a} - sqrt{b}) -sqrt{a} sqrt{a}+b }{ sqrt{a} ( sqrt{a} -    sqrt{b} )} } =
 frac{a-b-a+b }{sqrt{a}(sqrt{a}-sqrt{b})}}=frac{0}{sqrt{a}(sqrt{a}-sqrt{b})}}=0
Самые новые вопросы